Porous bone grafting-free window type interbody fusion cage and preparation method thereof
Through the design of porous typeless bone -shaped window -type vertebrate fusion, 3D printing and nano -material technology are used to solve the problem of existing intervertebral fusion device that requires additional bone planting or use BMPS, realizing simplifying surgery, improving biological activity and reducing reduction The effect of infection risk.
Patent Information
- Application Number
- CN202411700422.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-21
AI Technical Summary
In the design of existing intervertebral fusion devices, intermediate bone graft windows are usually reserved, requiring additional bone grafts or BMPs bone growth factors, which increases the difficulty and cost of surgery and is prone to induce infection.
Design a porous -type bone -free window -type vertebral fusion, printed by 3D printed framework with a hollow structure, fills the porous structure inside, sets up a bite tooth and clamp structure, the surface coating nano -hydroxygenyhys Stone or polydamine to improve biological activity.
The design of non -bone windows simplifies the surgical process. The porous structure provides a hole in the bone tissue. The surface coating improves biological activity, enhances the integration of intervertebral fusion and vertebral body, and reduces the risk of infection.
Smart Images

Figure CN119326561A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of orthopedic implants, and in particular relates to a porous bone-graft-free window-type intervertebral fusion device and a preparation method thereof. Background Art
[0002] The number of patients with spinal injuries caused by factors such as an aging population and traffic accident trauma is huge, and spinal fusion plays an important role in the treatment of these patients.
[0003] Although there are many types of intervertebral fusion systems on the market, the materials used include titanium and its alloys, tantalum and other medical metals, PEEK and other medical polymers, allogeneic bone, etc., and the preparation process is mainly based on traditional precision machining, but generally a middle bone grafting window is reserved in the design, and it mainly relies on auxiliary filling of autologous bone or BMPs bone growth factors to ensure rapid fusion between the upper and lower vertebrae to achieve the treatment purpose.
[0004] However, clinical use requires additional bone grafting or the addition of BMPS bone growth factor, which makes the surgery more difficult, the process more complicated, and the price more expensive. In addition, improper selection and processing of bone can easily induce infection. Summary of the invention
[0005] The purpose of the present invention is to provide a porous bone-graft-free window-type intervertebral fusion cage and a preparation method thereof.
[0006] In order to solve the above technical problems, the present invention provides a porous bone-graft-free window-type intervertebral fusion cage, comprising:
[0007] The frame body includes four side faces and two end faces, and the four side faces are all hollow structures;
[0008] The porous structure is filled in the space enclosed by the frame;
[0009] Engaging teeth are arranged on the upper and lower surfaces of the frame body; and
[0010] The clamping structure is arranged at one end of the frame body.
[0011] In one embodiment of the present application, the unit types of the porous structure include: triangular pyramid structure, cubic structure, rhombic dodecahedron structure, diamond structure, truncated octahedron structure, and three-dimensional Thiessen polygon structure.
[0012] In one embodiment of the present application, the porous structure includes at least one of the following features:
[0013] The rod diameter of the porous structure is 100-800 μm;
[0014] The pore size of the porous structure is 200-1000 μm;
[0015] The porosity of the porous structure is 20-90%.
[0016] In one embodiment of the present application, at least a portion of the surface of the porous bone-graft-free window-type intervertebral fusion cage is provided with a nano-hydroxyapatite coating.
[0017] In one embodiment of the present application, an optional method for preparing a porous bone-graft-free window intervertebral fusion cage includes:
[0018] The intervertebral fusion device prepared by 3D printing was placed in a 60°C 5M NaOH solution for 6-8 hours, taken out and rinsed with deionized water until the pH value was 7, and placed in a 60-80°C oven for drying for 24 hours to obtain an intervertebral fusion device after alkaline heat treatment;
[0019] The intervertebral fusion cage after alkali heat treatment is immersed in nano-hydroxyapatite slurry and ultrasonically treated for 10-30 minutes;
[0020] After the nano-hydroxyapatite slurry is filled into the porous structure of the intervertebral fusion cage after alkali heat treatment, the slurry is taken out, centrifuged at a speed of 100-500 rpm / min for 1-2 minutes, and placed in a 60-80°C oven for drying;
[0021] The dried intervertebral fusion cage was placed in a muffle furnace and heat treated at 600°C for 1-2 hours.
[0022] In one embodiment of the present application, at least a portion of the surface of the porous bone-graft-free window-type intervertebral fusion cage is provided with a polydopamine layer and a nano-hydroxyapatite coating.
[0023] In one embodiment of the present application, an optional method for preparing a porous bone-graft-free window intervertebral fusion cage includes:
[0024] The intervertebral fusion device prepared by 3D printing was placed in a 60°C 5M NaOH solution for 6-8 hours, taken out and rinsed with deionized water until the pH value was 7, and placed in a 60-80°C oven for drying for 24 hours to obtain an intervertebral fusion device after alkaline heat treatment;
[0025] The intervertebral fusion cage after alkali heat treatment was immersed in the dopamine solution and stirred continuously at 200-400 rpm for 12-16 hours to coat the surface of the intervertebral fusion cage with polydopamine, and then washed with deionized water for 3-5 times and dried in an oven at 40-60°C;
[0026] The dried intervertebral fusion device is immersed in the nano-hydroxyapatite slurry and subjected to ultrasonic treatment for 10-30 minutes. After the nano-hydroxyapatite slurry is filled into the porous structure of the intervertebral fusion device after the alkali heat treatment, it is taken out, centrifuged at a speed of 100-500 rpm / min for 1-2 minutes, and placed in a 60-80°C oven for drying again;
[0027] The polydopamine layer and nanohydroxyapatite coating process can be repeated 2-3 times;
[0028] The dried intervertebral fusion cage was placed in a muffle furnace and heat treated at 600°C for 1-2 hours.
[0029] In one embodiment of the present application, the method for preparing the dopamine solution comprises:
[0030] Prepare 10-15 mmol / L tris(hydroxymethyl)aminomethane hydrochloride solution with deionized water or pure water;
[0031] Dopamine powder is added to the tris(hydroxymethyl)aminomethane hydrochloride) solution at a concentration of 1-4 mg / ml, and the pH of the solution is adjusted to 8-9 to obtain the dopamine solution.
[0032] The beneficial effects of the present invention are:
[0033] 1. The design without bone grafting window reduces the complexity of the use process, facilitates operation, and reduces the possibility of contamination of the fusion device;
[0034] 2. 3D printing can be used to create a porous structure with bionic trabeculae, which can effectively provide channels for bone tissue growth and a surface that is conducive to cell adhesion, so that new bone can grow into the fusion device through micropores and adhere to the surface of metal trabeculae, forming a close combination of bone and implant;
[0035] 3. The hydroxyapatite coating, nano-hydroxyapatite coating or the polydopamine layer and nano-hydroxyapatite coating improve the biological activity of the surface of the matrix material and enhance the interface integration between the intervertebral fusion device and the upper and lower end plates of the vertebral body.
[0036] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description and the drawings.
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figures 1 to 5 are stereoscopic views of some embodiments of the porous bone-graft-free window intervertebral fusion cage of the present invention;
[0040] Figure 6 It is a schematic diagram of a triangular pyramid structure;
[0041] Figure 7 It is a schematic diagram of the cubic structure;
[0042] Figure 8 It is a schematic diagram of the structure of a rhombic dodecahedron;
[0043] Fig. 9 is a schematic diagram of the diamond structure;
[0044] Fig.10 is a schematic diagram of a truncated octahedron structure;
[0045] Fig.11 It is a schematic diagram of a three-dimensional Thiessen polygon structure;
[0046] Fig.12 It is a schematic diagram of a spike-type biting tooth;
[0047] Fig.13 It is a schematic diagram of wedge-shaped bite teeth;
[0048] Fig.14 It is a schematic diagram of a barbed-hook type biting tooth;
[0049] Fig.15 The samples were treated with alkali heat;
[0050] Fig.16 This is the sample treated with polydopamine solution;
[0051] Fig.17 This is a scanning electron microscope picture of the sample treated with polydopamine;
[0052] Fig.18 This is the sample treated with nano-hydroxyapatite slurry;
[0053] Fig.19 This is a scanning electron microscope photo of the sample after being treated with nano-hydroxyapatite slurry.
[0054] In the figure:
[0055] Frame body 1, porous structure body 2, engaging teeth 3, clamping structure 4, threaded hole 41, clamping notch 42. DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] See also Figures 1 to 5 In some embodiments of the present application, a porous bone-graft-free window-type intervertebral fusion device includes: a frame body 1, which includes four side faces and two end faces, and the four side faces are hollow structures; a porous structure body 2, which fills the space enclosed by the frame body 1; engaging teeth 3, which are arranged on the upper and lower surfaces of the frame body 1; and a clamping structure 4, which is arranged at one end of the frame body 1.
[0058] In this embodiment, optionally, the frame body 1 may be a solid frame, which, as the main load-bearing structure, can provide sufficient strength for the intervertebral fusion cage. Figures 1 to 5 In some embodiments, the four side surfaces of the frame body 1 are all hollow structures; the two end surfaces can be both closed, or designed as two hollow types according to needs, or one closed type and one hollow type.
[0059] In this embodiment, optionally, the unit type of the porous structure 2 may be, but is not limited to, a triangular pyramid structure, a cubic structure, a rhombic dodecahedron structure, a diamond structure, a truncated octahedron structure or a three-dimensional Thiessen polygon structure.
[0060] Furthermore, the porous structure 2 is evenly filled inside the frame 1 and can be filled into the hollow structure of the frame 1 for bone tissue to grow in; a support beam can be provided inside or on the surface of the porous structure; see Figures 6 to 11 The unit type of the porous structure 2 may be, but is not limited to, a triangular pyramid / G7 structure, a cubic structure, a rhombic dodecahedron structure, a diamond structure, a truncated octahedron structure or a three-dimensional Thiessen polygon structure; the rod diameter of the porous structure 2 may be 100-800 μm; the pore diameter of the porous structure 2 may be 200-1000 μm; the porosity of the porous structure 2 may be 20-90%.
[0061] In this embodiment, optionally, the occlusal teeth 3 located on the same surface may be symmetrically distributed, and the occlusal teeth 3 are used to occlude into the upper and lower end plates of the vertebral body to maintain the stability of the intervertebral fusion cage.
[0062] For further information, see Figure 12 to Figure 14 The engaging teeth 3 may be, but are not limited to, spike-shaped, wedge-shaped or barbed-shaped.
[0063] In this embodiment, the clamping structure 4 disposed at the end of the frame body 1 can clamp the intervertebral fusion cage during operation.
[0064] In some embodiments, the clamping structure 4 may be a clamping notch 42, for example Figure 1 The clamping notch 42 is convenient for clamping with pliers.
[0065] In some embodiments, the clamping structure 4 may include a threaded hole 41 and clamping notches 42 located on both sides of the threaded hole 41. Figure 2 and Figure 4 .
[0066] In some embodiments, the clamping structure 4 can be a threaded hole 41, see Figure 3 ; It can also be 3 threaded holes 41, see Figure 5 .
[0067] In this embodiment, preferably, the porous bone-graft-free window-type intervertebral fusion cage is made in one piece by 3D printing; its raw material may be but is not limited to titanium, titanium alloy, tantalum or polyetheretherketone.
[0068] In this embodiment, further, in order to improve the problem of insufficient activity and poor intervertebral fusion and interface healing ability caused by the inherent inertness of the intervertebral fusion device material, a hydroxyapatite coating, a nano-hydroxyapatite coating or a polydopamine layer and a nano-hydroxyapatite coating can be provided on the surface of the porous bone-free window intervertebral fusion device.
[0069] It should be noted that the hydroxyapatite coating, nano-hydroxyapatite coating or polydopamine layer and nano-hydroxyapatite coating are provided on the surface of the porous non-bone graft window intervertebral fusion cage, which can be achieved by using existing processes, and can be achieved by the following methods:
[0070] As an optional method for forming the hydroxyapatite coating, the hydroxyapatite coating may be formed by vacuum plasma spraying, covering the end surface except the end surface where the clamping structure 4 is provided, and the thickness may be 30-200 μm.
[0071] As an optional method for forming the nano-hydroxyapatite coating, a dip coating method may be used to cover the surface of the porous structure 2 and the upper and lower surfaces of the frame 1, and the thickness may be 20-100 μm.
[0072] The specific steps are as follows:
[0073] The intervertebral fusion device prepared by 3D printing is subjected to alkaline heat treatment, that is, the intervertebral fusion device is placed in a 60℃ 5M NaOH solution for 6-8h, taken out and rinsed with deionized water until the pH is 7, and placed in a 60-80℃ oven for drying for 24h to obtain an intervertebral fusion device after alkaline heat treatment. It is immersed in nanohydroxyapatite slurry and ultrasonically treated for 10-30min. After the nanohydroxyapatite slurry is filled into the porous structure of the intervertebral fusion device after alkaline heat treatment, it is taken out, centrifuged at a speed of 100-500rpm / min for 1-2min, and placed in a 60-80℃ oven for drying. The coating process can be repeated 2-3 times. The dried intervertebral fusion device is placed in a muffle furnace and heat treated at 600℃ for 1-2h.
[0074] The polydopamine layer and the nano-hydroxyapatite coating can also be coated on the surface of the porous structure 2 and the upper surface of the frame 1 by dip coating, and the thickness can be 20-100 μm.
[0075] The specific steps are as follows:
[0076] The intervertebral fusion device prepared by 3D printing was subjected to alkaline heat treatment, that is, the intervertebral fusion device was placed in a 60°C 5M NaOH solution for 6-8 hours, taken out and rinsed with deionized water until the pH value was 7, and placed in a 60-80°C oven for drying for 24 hours to obtain the intervertebral fusion device after alkaline heat treatment. Fig.15 These are samples after alkali heat treatment.
[0077] The intervertebral fusion cage after alkali heat treatment was immersed in the dopamine solution and stirred continuously at 200-400 rpm for 12-16 hours to coat the surface of the intervertebral fusion cage with polydopamine, and then washed with deionized water for 3-5 times and dried in an oven at 40-60°C. Fig.16 These are samples treated with polydopamine solution. Fig.17 This is a scanning electron microscope image of the sample after polydopamine treatment.
[0078] Immerse it in nano-hydroxyapatite slurry, ultrasonically treat it for 10-30 minutes, take it out after the nano-hydroxyapatite slurry is filled into the porous structure of the intervertebral fusion cage after alkali heat treatment, centrifuge it at a speed of 100-500rpm / min for 1-2 minutes, and place it in a 60-80℃ oven for drying. Fig.18 This is the sample treated with nano-hydroxyapatite slurry. Fig.19 This is a scanning electron microscope photo of the sample after being treated with nano-hydroxyapatite slurry.
[0079] The polydopamine layer and nano-hydroxyapatite coating process can be repeated 2-3 times. The dried intervertebral fusion device is placed in a muffle furnace and heat treated at 600°C for 1-2 hours.
[0080] The preparation method of the dopamine solution is as follows: deionized water or pure water is used to prepare a 10-15 mmol / L tris(hydroxymethyl)aminomethane hydrochloride solution; dopamine powder is added to the tris(hydroxymethyl)aminomethane hydrochloride solution at a concentration of 1-4 mg / ml, and the pH value of the solution is adjusted to 8-9 to obtain the dopamine solution.
[0081] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A porous non-bone graft window intervertebral fusion cage, characterized in that: include: The frame body includes four side faces and two end faces, and the four side faces are all hollow structures; The porous structure is filled in the space enclosed by the frame; Engaging teeth are arranged on the upper and lower surfaces of the frame body; and The clamping structure is arranged at one end of the frame body.
2. The porous non-bone graft window intervertebral fusion cage according to claim 1, characterized in that: The unit types of the porous structure include: triangular pyramid structure, cubic structure, rhombic dodecahedron structure, diamond structure, truncated octahedron structure, and three-dimensional Thiessen polygon structure.
3. The porous non-bone graft window intervertebral fusion cage according to claim 1, characterized in that: The porous structure comprises at least one of the following characteristics: The rod diameter of the porous structure is 100-800 μm; The pore size of the porous structure is 200-1000 μm; The porosity of the porous structure is 20-90%.
4. The porous non-bone graft window intervertebral fusion cage according to claim 1, characterized in that: At least part of the surface of the porous bone-graft-free window-type intervertebral fusion cage is provided with a nano-hydroxyapatite coating.
5. The method for preparing the porous bone-graft-free window intervertebral fusion cage according to claim 4, characterized in that: include: The intervertebral fusion device prepared by 3D printing was placed in a 60°C 5M NaOH solution for 6-8 hours, taken out and rinsed with deionized water until the pH value was 7, and placed in a 60-80°C oven for drying for 24 hours to obtain an intervertebral fusion device after alkaline heat treatment; The intervertebral fusion cage after alkali heat treatment is immersed in nano-hydroxyapatite slurry and ultrasonically treated for 10-30 minutes; After the nano-hydroxyapatite slurry is filled into the porous structure of the intervertebral fusion cage after alkali heat treatment, the slurry is taken out, centrifuged at a speed of 100-500 rpm / min for 1-2 minutes, and placed in a 60-80°C oven for drying; The dried intervertebral fusion cage was placed in a muffle furnace and heat treated at 600°C for 1-2 hours.
6. The porous non-bone graft window intervertebral fusion cage according to claim 1, characterized in that: At least part of the surface of the porous bone-graft-free window-type intervertebral fusion device is provided with a polydopamine layer and a nano-hydroxyapatite coating.
7. The method for preparing the porous bone-graft-free window intervertebral fusion cage according to claim 6, characterized in that: include: The intervertebral fusion device prepared by 3D printing was placed in a 60°C 5M NaOH solution for 6-8 hours, taken out and rinsed with deionized water until the pH value was 7, and placed in a 60-80°C oven for drying for 24 hours to obtain an intervertebral fusion device after alkaline heat treatment; The intervertebral fusion cage after alkali heat treatment was immersed in the dopamine solution and stirred continuously at 200-400 rpm for 12-16 hours to coat the surface of the intervertebral fusion cage with polydopamine, and then washed with deionized water for 3-5 times and dried in an oven at 40-60°C; The dried intervertebral fusion device is immersed in the nano-hydroxyapatite slurry and subjected to ultrasonic treatment for 10-30 minutes. After the nano-hydroxyapatite slurry is filled into the porous structure of the intervertebral fusion device after the alkali heat treatment, it is taken out, centrifuged at a speed of 100-500 rpm / min for 1-2 minutes, and placed in a 60-80°C oven for drying again; The polydopamine layer and nanohydroxyapatite coating process can be repeated 2-3 times; The dried intervertebral fusion cage was placed in a muffle furnace and heat treated at 600°C for 1-2 hours.
8. The method for preparing the porous bone-graft-free window intervertebral fusion cage according to claim 7, characterized in that: The preparation method of the dopamine solution comprises: Prepare 10-15 mmol / L tris(hydroxymethyl)aminomethane hydrochloride solution with deionized water or pure water; Dopamine powder is added to the tris(hydroxymethyl)aminomethane hydrochloride) solution at a concentration of 1-4 mg / ml, and the pH of the solution is adjusted to 8-9 to obtain the dopamine solution.
Citation Information
Cited By
Bionic interbody fusion cage with piezoelectric multifunctional coating
CN122075195A